An overview of the pollination interactions between the ginger family (Zingiberaceae) and insects in Asia - Suganthi APPALASAMY; Nivaarani ARUMUGAM; Visweswara Rao PASUPULETI; Sreeramanan SUBRAMANIAM; Jayaraj Vijaya KUMARAN; Maryana Mohamad NOR; Mohammed Abdus SALAM (European Journal of Entomology, 2023)
The plant-biotic pollinator interaction is crucial for the survival of both organisms. Insects are recognised as effective biotic pollinators. As there are few specific studies on the pollination of angiosperms, the emphasis of this review is on understanding the pollination process by reviewing the knowledge of the ginger-insect pollinator interaction in Asia. Currently the plant-pollinator interaction of only 5% of Asian species of Zingiberaceae is evaluated. Previous studies indicate that bees, such as, halictid and blue-banded bees are, among the many floral vistors, the most important pollinators of ginger plants in Asia. Knowledge of non-bee pollinators is still scarce. In order to obtain a more detailed understanding of the interrelationship of the pollinators of ginger plants with the morphology of their flowers, floral scent and geographical factors, further research is needed.